The Influence Of Product Differentiation Strategies, Brand Image And Service Quality On Purchasing Decisions At Omah Pentol Café In Munjungan District - Nurohman, Alfan; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to analyze whether there is a significant influence between the variables of product differentiation, brand image and service quality on purchasing decisions at the Omah Pentol café in Munjungan district. Design/Method/Approach : Nonprobability sampling approaches and a quantitative approach are employed in this study. The 40 respondents who had made purchases at Rumah Pentol Café served as the research's samples. They were subjected to analysis using the traditional assumption test, multiple linear regression analysis, coefficient of determination, and test. The population for this study consisted of all customers who had made purchases there. utilizing the SPSSv23 tools, hypotheses Research Findings : According to the research's findings, Pentol House Café customers' decisions to buy are somewhat influenced by service quality and product difference. In the meanwhile, decisions to buy are not partially influenced by brand image. Brand image, service quality, and product distinction all have a big impact at the same time. Theoretical contribution/Originality : Product differentiation can expand understanding of how to increase sales which can influence consumer behavior and purchasing decisions. Measuring the impact and preferences of consumers on service quality, and digging deeper into the concept of brand image from a consumer perspective influences purchases. Practitioner/Policy implications: This research provides practical implications for Pentol House Cafés in improving purchasing decisions Research limitations: Only the independent variables—brand image, product distinctiveness, and service quality—and the dependent variable—product quality—are included in this study. Further investigation is required to determine the additional variables that continue to affect the dependent variable.